Attitudes development of Occupational Therapy Interns from a private school in three clinical settings a descriptive study - Medallon, Kim Gerald G.; Fajutagana, Nemuel S. (Manila The National Teacher Training Center for the Health Professions, 2015)
The purpose of this study is to describe the current status of attitudes development of occupational therapy interns from a private school in three clinical settings. It aims to identify the attitudes that are being demonstrated, determine their consistency and extent of manifestation, identify the factors facilitating and/or impeding their consistent and full extent manifestation, determine the current knowledge, attitude, and skills of OT clinical teachers in attitudes development, and to identify the utilized teaching-learning strategies. Methods: This study utilized a quantitative cross-sectional design involving observation, in-depth interviews, and reviewing of documents to attain the research objectives. OT clinical teachers and interns of the University of Santo Tomas rotating in the National Capital Region were invited and participated in this study. Descriptive and content thematic analyses were used for data analysis. Results: It is observed that the three different clinical settings presented little variety in the set of attitudes being manifested by the OT interns. The attitudes that were commonly manifested in the three settings were: initiative, adaptation, patience, and collaborative practice. Negative attitudes such as irresponsibility and special preference were also observed. A certain attitude's manifestation is influenced by the dynamic transaction among the OT intern, client, presenting difficulty and context during a typical service delivery. Most of the attitudes that were observed and/or reported were lacking consistency in terms of its manifestation. Clinical teachers frequently stressed that the current interns would still need continuous prompts, cues and reminders just to enact these attitudes. The extent of manifestation of the identified attitudes may be described as being smaller and narrower in scope as compared to the set and expected affective outcomes in the training manuals, standards of practice, and code of ethics. The attitudes that are currently manifested are generally caused by factors outside the direct training received in the classroom and affiliations. They include overall internship experience, classroom experience, sense of camaraderie, personal convictions and reflections, preference for a setting, upbringing, and culture. Factors facilitating and impeding a consistent and full extent manifestation of attitudes were also identified. These factors may pertain to the OT intern, clinical teacher, peers, learning opportunities, and features of the center. The gap formed between what can be ideally attained and what is currently manifested is brought about by a multitude of contextual factors hindering the attainment of this inherent potential. These factors may point to the person such as limited knowledge and weak skills of the clinical teacher and personal factors of the intern; the task itself such as vague specification of affective outcomes, insufficient content areas, limited teaching-learning strategy, weak instruction, and limited pre-internship preparation; and the environment such as limited expectations on the part of the clinical teacher and limited features of the center. Implications: Results of this study may pave the way to possible policy and curriculum changes to ensure that attitudes would not just be listed as learning outcomes but would really be emphasized in the teaching-learning process. Improving the quality of the learning outcomes and instruction, through remediating the identified contextual factors, would be helpful in producing future occupational therapists who are supporting health and participation in life through engagement in occupation in a holistic, humane and ethical manner.
Thesis (Master of Health Professions Education)--University of the Philippines Manila, June 2015
Panel Members: Nemuel S. Fajutagana MD MHPEd, Chair/Adviser; Maria Elizabeth M. Grageda PTRP MHPEd, Reader/Critic; Melflor A. Atienza MD, MHPEd, Member;Nomar M. Alviar MD MHPEd, Member; Carmelo C. Cunanan PTRP, PhD, Member.
Keywords: Attitudes development